2014
DOI: 10.1177/0004865814524423
|View full text |Cite
|
Sign up to set email alerts
|

The pros and cons of prohibiting drugs

Abstract: In September 2012, a group known as Australia 21 called for a rethink on the prohibition against illegal drugs. If the response from Australian Federal, State, and Territory Governments is any guide, the call fell on deaf ears. In recent years, even scholarly debate about the merits of prohibition appears to have subsided. This paper acknowledges that social and financial costs of the prohibition against illegal drugs but argues that prohibition also prevents a great deal of harm. The multifarious nature of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Throughout Europe, eight in every 100—that is, a total of 400 000—16 year olds use cannabis monthly 5. It’s reasonable to assume that some 16 year olds will be tipped from non-use into use by the absence of any risk of a criminal consequence 67. Qualitative research indicates that many young people report the illegal status of cannabis as a deterrent 67.…”
Section: Yes—bobby Smyth Mary Cannon Andrew Molodynskimentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout Europe, eight in every 100—that is, a total of 400 000—16 year olds use cannabis monthly 5. It’s reasonable to assume that some 16 year olds will be tipped from non-use into use by the absence of any risk of a criminal consequence 67. Qualitative research indicates that many young people report the illegal status of cannabis as a deterrent 67.…”
Section: Yes—bobby Smyth Mary Cannon Andrew Molodynskimentioning
confidence: 99%
“…It’s reasonable to assume that some 16 year olds will be tipped from non-use into use by the absence of any risk of a criminal consequence 67. Qualitative research indicates that many young people report the illegal status of cannabis as a deterrent 67. Even if only two in every 92 current non-users were tipped into use this would mean an extra 100 000 of Europe’s 16 year olds using cannabis monthly, resulting in thousands of additional cases of dependence, depression, anxiety, and psychosis 23…”
Section: Yes—bobby Smyth Mary Cannon Andrew Molodynskimentioning
confidence: 99%
“…Weatherburn argues (Weatherburn, 2014), without providing supportive data, that drug law enforcement increased the price of street drugs and that increased prices reduced consumption. He argues by analogy with tobacco that reduced consumption of illicit drugs is likely to reduce harm.…”
Section: Pricementioning
confidence: 99%
“…Weatherburn argues (Weatherburn, 2014) that drug prohibition has been an effective policy while advancing plausible mechanisms for its effectiveness. But Weatherburn has not demonstrated that drug prohibition has reduced drug production, drug consumption or drug-related harms.…”
Section: Introductionmentioning
confidence: 99%
“…As in many places in the world, the ineffectiveness of the state regulatory authority (Roitman, 2004) opened the door for the escalation of the private use of violence and armed disputes between these groups. On the one hand, illegal drug markets absorb and intensify non-lethal and lethal violence in the social environments in which they operate (Ruggiero, 2000), a point not acknowledged by prohibition supporters (Weatherburn, 2014). On the other hand, the different trajectories of control of the drug market and any associated violence in both South African cities reflect a complex interaction between local and foreign entrepreneurs of violence and the police themselves, who intervened when that violence became too egregious or inconvenient.…”
mentioning
confidence: 99%